Posttransplant Infectious Complications: A Prospective Study on 142 Kidney Allograft Recipients - Shahram Moosavi; Ali Saraji; Reza Ebrahimi; Mohammadreza Nikoobakht; Mohsen Taheri Mahmoudi; Abdorasoul Mehrsai; Sepehr Salem; Mohammadreza Pourmand; Gholamreza Pourmand; Babak Saboury (Urology Journal, 2006)
Introduction: We evaluated the posttransplant complications resulting from infections and their association with graft function, immunosuppressive drugs, and mortality. Materials and Methods: A total of 142 kidney allograft recipients were followed for 1 year after transplantation. The patients’ status was assessed during regular visits, and data including clinical characteristics, infections, serum creatinine level, acute rejection episodes, immunosuppressive regimen, graft function, and mortality were recorded and analyzed. Results: Infections occurred in 77 patients (54%). The lower urinary (42%) and respiratory (6.3%) tracts were the most common sites of infection. The most frequent causative organisms were Klebsiella in 34 (24%) and cytomegalovirus in 25 patients (18%). Wound infection occurred in 7 patients (5%). The mortality rate was 7.7% and infection-related death was seen in 5 patients (3.5%) who developed sepsis. Graft loss was seen in 16 patients (11%), of whom 2 developed cytomegalovirus infection, 2 experienced urinary tract infection, and 5 developed sepsis and died. Mycobacterial and hepatitis C infections were noticeably rare (0.7% and 2.8%, respectively). Conclusion: This study showed that infections are important causes of morbidity and mortality during the posttransplant period. We recommend that serologic tests be performed before and after transplantation to recognize and meticulously follow those who are at risk. In our study, high-risk patients were those with elevated serum creatinine levels who received high doses of immunosuppressive drugs. As the urinary tract is the most common site of infection, early removal of urethral catheter is recommended to reduce the risk of infection.